Literatur Review : Analisis Faktor Kepemilikan Jaminan Kesehatan Nasional Menuju Universal Health Coverage - Maryanto, Hendri; Misnaniarti, Misnaniarti; Idris, Haerawati; Fajar, Nur Alam (Poltekkes Kemenkes Kendari, 2023)
Introduction: A country's National Health Insurance Program aims to achieve Universal Health Coverage and guarantee that every citizen has access to healthcare. Objective: To evaluate aspects related to involvement in National Health Insurance, challenges faced, and efforts made to maintain and increase engagement. Method: Researchers use simple data analysis techniques (simplified approach). Researchers have selected 12 national and 8 international articles for research. Results: This study shows that three main factors influence involvement in the Health Social Security Administration Agency: predisposing factors, supporting factors, and need factors. Predisposing factors include age, gender, education, occupation, and number of families. Conclusion: Age, gender, education, occupation, and number of family members are predisposing factors. Possible factors are knowledge, income, and family support, while need factors are family perceptions and desires. The study not only found components but also found barriers that affect participation in National Health Insurance and efforts that can increase participation elements.